Sukcesja wtórna drzew w krajobrazie wydmowym stałej powierzchni badawczej Glinki w świetle analizy GIS - Sewerniak, Piotr; Mendyk, Łukasz (Leśne Prace Badawcze, 2026)
The aim of the study was to present the main characteristics of the “Glinki” research area together with results of the first measurements on tree number, density, distribution and species composition carried out in 2011. The research was conducted in a free-of-forest management part of the Toruń military area which is located in one of the biggest inland dune fields of Europe. The “Glinki” research area was established in 2011 and consists of two plots (together 26.3 ha), which are in close proximity to each other. After the last fire in 1991, secondary succession has been the main factor shaping vegetation on both plots. For every plot, the location of all trees of at least 1 m height (560 in plot I and 292 in plot II) was determined. These measurements were subjected to spatial analysis in ArcGIS 9.3 with special emphasis on the exposure of the dune slopes. The main tree species on both plots were Scots pine, Pinus sylvestris , and birch, Betula pendula , (82 % and 17 % of all trees respectively). Tree density 20 years after the last fire was very low (32 trees/ha), which mainly resulted from the lack of a sufficient source of seeds in the close vicinity of the plots during the first years after the fire. We also found that tree distribution was related to the main direction of seed inflow and land relief. Tree density was much higher on dune slopes with a northern exposure when compared to other slope exposures, which resulted from different site conditions on the different slopes.